Factors contributing to Self-Medication among adults aged 18-50 years in Lyamutundwe Village, Busiro County, Wakiso District. A Cross-sectional Study. - Monica Munyambabazi; Prosper Mubangizi (Student's Journal of Health Research, 2022)
Background: Self-medication is the use of drugs to treat self-diagnosed disorders or symptoms. The purpose of the study is to assess the factors contributing to self-medication among adults aged 18-50 years in Lyamutundwe village, Busiro County, Wakiso district. Methodology: The study design used was a descriptive cross-sectional study with a purposive sampling technique as sampling technique. Data were collected on a sample of 50 respondents using structured questionnaires and later analyzed manually using tally sheets and presented in frequency distribution tables and figures with the support of narratives. Results: Findings related to individual factors contributing to self-medication reported that 78% of the respondents had kept some medications at home, 68% had someone self-medicating at home, 56% had medical personnel in the family, 70% usually took medicines that remained home, 78% took medicine without first visiting the hospital, 41% had taken medicines without prescription more than thrice, 60% self-medicated more in pain killers. 94% of the respondents had pharmacies/ drug shops around their homes, 85% were influenced by the pharmacies/drug shops to buy drugs whenever they got sick before visiting a health practitioner, and 68% had ever been recommended drugs by a community member. Conclusion: The researcher, therefore, concluded that most individuals practiced self-medication since most of them found it time-saving and affordable for them. Recommendation: Individuals should always first attain prescriptions before taking any drug and conducting community sensitization programs by public health officers to create awareness of the dangers of self-medication